RESPON FREKUENSI PEMBERIAN PUPUK ORGANIK CAIR AIR CUCIAN BERAS DAN MEDIA TANAM TERHADAP PERTUMBUHAN SEEDLING ANGGREK LARAT (Larat bigibbum var. schoederianum (Rchb.f. ex W.Watson) Peter B.Adams - Hartanti, Apriia; Su'ud, Mochamad; Ghozali, Muchlas (Agrotechbiz : Jurnal Ilmiah Pertanian, 2024)
This study aims to identify the effects of liquid organic fertilizer derived from rice washing water (POC air cucian beras) and different planting media on the growth of Larat bigibbum var. schoederianum seedlings. Fertilizer application was done at Frekuensis of every 2 days, 4 days, and 6 days, using three types of planting media: moss, fern, and coconut husk. The study used a randomized complete block design (RCBD) with two factors: the first factor being the Frekuensi of POC air cucian beras application and the second factor being planting media. Various growth parameters such as plant height, leaf number, stem diameter, root length, and root number were monitored. The data were analyzed using analysis of variance (ANOVA), followed by DMRT 5% test to identify significant differences between treatments. The results of this study are expected to provide useful information on the optimal care for Larat bigibbum seedlings, particularly in terms of efficient POC air cucian beras application and appropriate media selection. The findings are also expected to reveal the best fertilizer application Frekuensi and the most suitable planting media to support the growth of Larat bigibbum seedlings. This research is significant for the development of environmentally friendly cultivation techniques and for improving the productivity of orchid cultivation in the future. Keywords: POC air cucian beras, planting media, Larat bigibbum, fertilizer application Frekuensi, seedling growth.